Relationship between Quality of Work Life of Medical Staff and Quality of Patient Care - Amjad Mohammadi-Bolbanabad; Barzan Shirkhani; Samira Mohammadi; Heshmatollah Asadi; Abas Aghaei (Baqiyatallah University of Medical Sciences, 2016)
Background: Nowadays, quality of patient care is one of the major and important concerns of health care delivery which is extremely dependent on the medical staff. Objectives: The purpose of this study was to investigate the relationship between Quality of Work Life (QWL) and quality of patient care. Methods: This study was a descriptive-analytic study based on correlation which was conducted in the educational hospitals of Kermanshah. A total of 320 medical staffs were selected for the study. Quality of Work Life and Quality of Patient Care questionnaires were used to collect the data. For data analysis, descriptive statistics, person correlation coefficient, t-test and multivariate regression were used by using SPSS16 Results: Data analysis showed that the Quality of Work Life of medical staffs was in a medium level. Our findings indicate that there is a significant, negative relationship between stress at work and quality of patient care (P-value=0.001 & r=-0.247) and there is a significant, positive relationship between control & job satisfaction and quality of patient care (P-value=0.001 & r=0.217). Results of multivariate regression analysis showed that stress at work net account for 6% of the variance of the quality of patient care. Conclusion: Focusing on improving the working conditions of medical staffs can be incredibly useful in increasing the quality of health care.